Design and application of water treatment technology for Karya Makmur Hamlet, Batuah Village, Loa Janan District, Kutai Kartanegara - Sirajuddin Sirajuddin; Firman Firman; Harjanto Harjanto; Alwathan Alwathan; Sitti Sahraeni (Universitas Muhammadiyah Magelang, 2021)
The clean water service of PDAM Loa Janan Sub-district has not yet reached all villages, including Batuah Village, which has not yet received clean water services from the government. To meet the need for clean water for the people of Batuah Village, they use drilled well water, dug water that does not meet health standards because it contains heavy metals that are toxic (poisonous). This activity aims to meet the needs of clean water for the community in Batuah Village. Activities start from identifying the potential and quality of raw water sources which include physical, chemical and biological parameters, designing and manufacturing clean water treatment units as well as testing the quality of water products produced, socialization and training to partner groups on the process of operating clean water treatment technology and monitoring the sustainability of the water treatment process after being managed independently by the partner group.